MOTOR RESPONSE SPEED AND ITS RELATIONSHIP TO SOME DEFENSIVE SKILLS IN VOLLEYBALL - Younis Sabih Abdullah (Proximus Journal Publishing, 2025)
This research demonstrates the importance of identifying motor response speed in some basic volleyball skills. The researcher hypothesized the existence of statistically significant differences between motor response speed and some basic volleyball skills. The researcher used the descriptive approach because it suited the nature of the research, as well as for ease of access to data and information related to the research topic. The research sample consisted of 18 male and female volleyball players from Maysan Sports Club, who were selected intentionally. Chapter Four included a presentation, analysis, and discussion of the research results. The researcher used statistical tables to extract the values of arithmetic means and standard deviations for analysis, discussion, and study. Chapter Five included conclusions and recommendations. The researcher recommended the use of training on the skill of defending the court from movement among volleyball players at Maysan Sports Club.
Keywords: Skill; Defense; Volleyball